Beneficial Effects of Glucagon-Like Peptide-1 (GLP-1) in Diabetes-Induced Retinal Abnormalities: Involvement of Oxidative Stress - Hugo Ramos; Patricia Bogdanov; Joel Sampedro; Jordi Huerta; Rafael Simó; Cristina Hernández (MDPI AG, 2020)
Background: Hyperglycemia-induced oxidative stress plays a key role in diabetic complications, including diabetic retinopathy. The main goal of this study was to assess whether the topical administration (eye drops) of glucagon-like peptide-1 (GLP-1) has any effect on oxidative stress in the retina. Methods: db/db mice were treated with eye drops of GLP-1 or vehicle for three weeks, with db/+ mice being used as control. Studies included the assessment by western blot of the antioxidant defense markers CuZnSOD, MnSOD, glutathione peroxidase and reductase; immunofluorescence measurements of DNA/RNA damage, nitro tyrosine and Ki67 and Babam2 proteins. Results: GLP-1 eye drops protected from oxidative stress by increasing the protein levels of glutathione reductase, glutathione peroxidase and CuZnSOD and MnSOD in diabetic retinas. This was associated with a significant reduction of DNA/RNA damage and the activation of proteins involved in DNA repair in the retina (Babam2) and Ki67 (a biomarker of cell proliferation). Conclusions: GLP-1 modulates the antioxidant defense system in the diabetic retina and has a neuroprotective action favoring DNA repair and neuron cells proliferation.